Trust and Reciprocity: The Foundations of the Sharing Economy - Martini, Elvira; Vespasiano, Francesco (Italian Sociological Review, 2020)
The economic crisis that has hit hard on traditional markets and businesses, as well as the spread of digital platforms, have encouraged the emergence of new cultural practices and new forms of meeting between supply and demand for goods and services. Public attention has been directed towards new practices, such as the sharing economy, which expresses the emergence of a real revolution based on the culture of reuse and direct access. Practices, in other words, ‘connoted by the hybridization between formal and informal actions and oriented towards the re-embeddedness of economic exchange’ (Arcidiacono, 2013). Jeremy Rifkin (2014) prefigures a new ‘participatory economy’, made possible by digital technology and within ‘freedom of access exceeds the ownership, sustainability supplants consumerism, cooperation ousts competition. An economy where the logic of the delegation is overcome and all the actors interact and release new resources in order to identify and implement responses to their needs’. The aim of this work is to advance a reflection on how the sharing economy can help shape new forms of welfare, where social ties are increasingly the foundation of economic exchange and cooperation (Pais, Mainieri, 2015), looking at the potential of the community economy and the recovery of the reciprocity and sociality values.